AN ANALYSIS STUDENTS’ PROBLEM IN ENGLISH SPEAKING AT THE SECOND GRADE OF SMAN 1 POMALAA - La Ode Muh Idrus Hamid; Rais Abin; Meisi Meisi (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
One of the most difficult language skills to master is speaking. This also applied to SMAN 1 Pomalaa. The English teacher of the school stated that the speaking skills of the second-grade students